2014
DOI: 10.1371/journal.ppat.1004061
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Mechanism of the Mycobacterium ulcerans Virulence Factor, Mycolactone, Depends on Blockade of Protein Translocation into the ER

Abstract: Infection with Mycobacterium ulcerans is characterised by tissue necrosis and immunosuppression due to mycolactone, the necessary and sufficient virulence factor for Buruli ulcer disease pathology. Many of its effects are known to involve down-regulation of specific proteins implicated in important cellular processes, such as immune responses and cell adhesion. We have previously shown mycolactone completely blocks the production of LPS-dependent proinflammatory mediators post-transcriptionally. Using polysome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
249
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(275 citation statements)
references
References 61 publications
24
249
1
1
Order By: Relevance
“…On the other hand, other researchers reported that mycolactone inhibited the function of the Sec61 translocon [7,9,26]. Sec61 mediates antigen transport across endosomal membranes and affects cross-presentation in dendritic cells [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, other researchers reported that mycolactone inhibited the function of the Sec61 translocon [7,9,26]. Sec61 mediates antigen transport across endosomal membranes and affects cross-presentation in dendritic cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several in vitro studies have suggested that mycolactone could inhibit cytokine and chemokine production from immune cells such as T cells, macrophages, and dendritic cells [9][10][11][12][13]. These observations clearly suggested that mycolactone presents immunosuppressive effects and may have an important role in the successful infection of M. ulcerans in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycolactone is a polyketidederived macrolide produced by the human pathogen Mycobacterium ulcerans, which was recently identified as a potent Sec61 inhibitor (13)(14)(15)(16). Mycolactone diffuses passively across the plasma membrane to target the pore-forming subunit of the translocon (Sec61α) (13), leading to the proteasomal degradation of newly synthesized Sec61 clients blocked in translocation (17). In contrast to previously described Sec61 inhibitors, such as cotransin (18), mycolactone prevents the biogenesis of secretory and transmembrane proteins with minor selectivity toward Sec61 substrates, as well as uniformly high efficacy (13,16).…”
Section: Significancementioning
confidence: 99%
“…Contrary to wild-type strains, mycolactone-deficient mutants of M. ulcerans do not impair the capacity of T cells to produce interleukin-2 (IL-2) in animal models, showing that mycolactone is the cause of these cellular response defects (11). In vitro, nanomolar concentrations of mycolactone efficiently blocked the functional maturation of dendritic cells (12) and cytokine production by activated lymphocytes, monocytes, macrophages, and epithelial cells (13)(14)(15)(16)(17). Mycolactone also down-regulated the expression of L-selectin on naĂŻve T cells, profoundly affecting the lymphocyte homing and expansion upon antigenic stimulation in vivo (18).…”
Section: Introductionmentioning
confidence: 99%